Impact of Initial Heart Rate, Diastolic Pressure, and Pulse Pressure on Prognostic Outcomes in Heart Failure Patients with Mildly Reduced Ejection Fraction - Hu H; Liu Z; Zeng J; Jiang M (International Journal of General Medicine)
Hailong Hu,1,* Zhican Liu,2,* Jianping Zeng,1 Mingyan Jiang2 1Department of Cardiology, Xiangtan Central Hospital, The Affiliated Hospital of Hunan University, Xiangtan, 411100, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, Xiangtan Central Hospital, The Affiliated Hospital of Hunan University, Xiangtan, 411100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingyan Jiang, Director of Department of Pulmonary and Critical Care Medicine, Xiangtan Central Hospital, The Affiliated Hospital of Hunan University, Xiangtan, 411100, People’s Republic of China, Email jiangmingyan1979@163.com Jianping Zeng, Director of Heart Center, Xiangtan Central Hospital, Xiangtan, 411100, People’s Republic of China, Email 571725929@qq.comBackground: Heart rate, diastolic pressure, and pulse pressure are key modifiable factors influencing heart failure prognosis. While heart failure with mildly reduced ejection fraction (HFmrEF) is a distinct subgroup of heart failure, the prognostic impact of these hemodynamic parameters in this population remains unclear, necessitating focused investigation. This study aims to elucidate their effects on HFmrEF patient outcomes.Methods: We retrospectively analyzed 1,653 hFmrEF patients treated at Xiangtan Central Hospital (2015– 2020). Using decision tree classification, patients were categorized based on initial heart rate (≤ 77 bpm and > 77 bpm). The ≤ 77 bpm group was further divided by pulse pressure (≤ 37 mmHg and > 37 mmHg), and the > 77 bpm group by diastolic pressure (≤ 63 mmHg, 63– 100 mmHg, and > 100 mmHg). Multivariate COX regression assessed mortality associations.Results: With a median follow-up of 33 months, overall mortality was 21.7% for heart rates ≤ 77 bpm and 30.4% for > 77 bpm. Multivariate COX regression showed that among patients with heart rates ≤ 77 bpm, those with pulse pressure > 37 mmHg had a higher mortality risk than those with pulse pressure ≤ 37 mmHg (HR 3.184; 95% CI 1.008– 10.058; p=0.048). For patients with heart rates > 77 bpm, those with diastolic pressure 63– 100 mmHg had a lower mortality risk compared to ≤ 63 mmHg (HR=0.652, 95% CI: 0.450– 0.943, p=0.023), with the lowest risk in patients with diastolic pressure > 100 mmHg (HR=0.370, 95% CI: 0.205– 0.666, p=0.001).Conclusion: This study highlights that HFmrEF patients with heart rates ≤ 77 bpm and pulse pressure ≤ 37 mmHg had the lowest mortality risk, while those with heart rates > 77 bpm and diastolic pressure ≤ 63 mmHg faced the highest risk. These findings provide valuable insights for risk stratification and may guide personalized management of HFmrEF patients.Keywords: heart failure with mildly reduced ejection fraction (HFmrEF), initial heart rate, diastolic pressure, pulse pressure, decision tree classification